’Feminisation’ of politics. Social movements against austerity in Spain as catalysts for the political participation of women - Huke, Nikolai; Wöhl, Stefanie (Momentum Quarterly, 2018)
The article analyses gender relations in social movements and new left parties in Spain following the M-15 movement. It argues that while activists have been hesitant to embrace explicit feminist demands and identities, the organisational ‘grammar’ of the protests was permeated by ‘unconscious’ feminisms. First person politics, inclusive and interactive assemblies and care infrastructures transformed individual concerns into collective demands. Experiences of increased vulnerability became political; boundaries between ‘public’ and ‘private’ were redrawn. The effect was a strong role of women during the protests (e.g. in struggles against evictions), which persisted, albeit to a lesser extent, throughout the subsequently emerging new left parties such as Podemos and electoral platforms